Pressurized Hot Ethanol Extraction of Carotenoids from Carrot By-Products - Charlotta Turner (Molecules, 2012)
Carotenoids are known for their antioxidant activity and health promoting effects. One of the richest sources of carotenoids are carrots. However, about 25% of the annual production is regarded as by-products due to strict market policies. The aim of this study was to extract carotenoids from those by-products. Conventional carotenoid extraction methods require the use of organic solvents, which are costly, environmentally hazardous, and require expensive disposal procedures. Pressurized liquid extraction (PLE) utilizes conventional solvents at elevated temperatures and pressure, and it requires less solvent and shorter extraction times. The extraction solvent of choice in this study was ethanol, which is a solvent generally recognized as safe (GRAS). The extraction procedure was optimized by varying the extraction time (2–10 min) and the temperature (60–180 °C). β-Carotene was used as an indicator for carotenoids content in the carrots. The results showed that time and temperatures of extraction have significant effect on the yield of carotenoids. Increasing the flush volume during extraction did not improve the extractability of carotenoids, indicating that the extraction method was mainly desorption/diffusion controlled. Use of a dispersing agent that absorbs the moisture content was important for the efficiency of extraction. Analysing the content of β-carotene at the different length of extraction cycles showed that about 80% was recovered after around 20 min of extraction.